Pedestrians’ and Cyclists’ Preferences for Street Greenscape Designs - Lin, Alin; Lou, Jiankun (Promet - Traffic&Transportation, 2022)
In recent years, the public’s interaction with street green spaces has been increasing, leading to much more concern about its design. By using stated preference data from a discrete choice experiment and the multinomial logit model, this study investigates pedestrians’ and cy-clists’ landscape preference regarding street green space through an online survey based on a virtual street envi-ronment. The results show that trees are the most suitable to be planted symmetrically between the cycle track and sidewalk. Large size trees with large crown width and tall height are more preferred than common size trees. There are considerable differences in preferences for lo-cations of shrubs, hedges, flowers, and grass between cy-clists and pedestrians. Cyclists prefer grass by the cycle track the most and grass by the sidewalk the least. But for pedestrians, flowers, hedges, and grass by the sidewalk are positively significant. Buildings with green plants in their front yards are preferred over a monotonous facade or coffee seats. This study enriches the understanding of the public’s landscape preferences for streets sharing non-motorised lanes. The results also play a guiding role in people-oriented street green space designs of land-scape architects and governments.